Interaction of dietary replacements of fishmeal by protein blend and feeding frequency on growth performance and protein utilization of gibel carp (Carassius gibelio var. CAS V) - Yongning Yu; Yu Wang; Junyan Jin; Dong Han; Xiaoming Zhu; Haokun Liu; Zhimin Zhang; Yunxia Yang; Shouqi Xie (Animal Nutrition, 2025)
Feeding frequency represents a potential strategy to improve the utilization of protein sources by fish. This study investigated its impact on the utilization of protein blend in gibel carp. The dietary fishmeal was totally substituted with three protein blends consisting of Tenebrio molitor meal, Chlorella meal, Clostridium autoethanogenum protein, cottonseed protein concentrate, at ratios of 1:1:8:2, 1:1:6:4, and 1:1:4:6, respectively. During an 8-week feeding trial, a total of 960 healthy fish (18.10 g) were randomly assigned to eight groups, each with three replicates. Then they were fed either twice daily (two meals per day) or four times daily (four meals per day) with four different diets. Higher feeding frequency increased feed intake and intestinal trypsin activity (P < 0.05), and up-regulated the expression levels of genes related to amino acid or peptide transporter (pept1, y+lat2) and sensory receptors (casr, gprc6a, mglur4) in intestine (P < 0.05). Moreover, it accelerated muscle protein turnover by increasing free amino acid content, aspartate aminotransferase activity and akt1 transcript levels (P < 0.05), ultimately promoting growth. However, higher feeding frequency reduced protein apparent digestibility and feed efficiency (P < 0.05). Dietary blended proteins elevated trypsin and chymotrypsin activities (P < 0.01). Notably, the adverse effects observed with blended proteins (ratio at 1:1:8:2) on total essential amino acid digestibility and muscle protein metabolism-related gene expression were mitigated with increased feeding frequency, thus alleviating growth inhibition. Furthermore, the blended proteins at a ratio of 1:1:6:4 increased protein apparent digestibility (P < 0.05), down-regulated mstn expression level (P < 0.05), and up-regulated expression levels of genes related to protein synthesis (akt1, mtor, s6k1, eif4b, eif4e; P < 0.05); thereby promoting protein utilization and muscle growth at four meals per day. Overall, feeding frequency interacted synergistically with blended proteins to influence growth and protein utilization in gibel carp, and a protein blend with a ratio of 1:1:6:4 was a superior alternative to fishmeal at both feeding frequencies. Future strategies aimed at replacing dietary fishmeal should consider the role of feeding frequency as a critical factor.